A new parametrization for the radio emission of air showers applied to LOFAR data - Plaisier I. (EPJ Web of Conferences, 2019)
The energy and mass composition of cosmic rays influence how the energy density of the radio emission of air showers is distributed on the ground. A precise description of the radio profiles can, therefore, be used to reconstruct the properties of the primary cosmic rays. Here, such a description is presented, using a separate treatment of the two radio-emission mechanisms, the geomagnetic effect and the charge excess effect. The model is parametrized as a function that depends only on the shower parameters, allowing for a precise reconstruction of the properties of the primary cosmic rays. This model is applied to cosmic-ray events measured with LOFAR and it is capable of reconstructing the properties of air showers correctly.